Fabrication of optical fiber sensor for dissolved oxygen / Siti Aishah Saidi - Saidi, Siti Aishah (2014)
This paper presents the work on the fabrication of optical fiber sensor for oxygen gas in air and in aqueous state. In order to prepare the sensor, certain type of thin film layer was deposited on top of the glass substrate. The thin film deposited is Tetraethylorthosilicate(TEOS) mix with dye ruthenium and the technique used is spin coating. The spin coating speed is 2000rpm/min and temperature used for drying is 80°C for each layer of sample for 5 minute. For this project TEOS were doped with the complex [RuII-tris(4-7-diphenyl-1,10-phenanthroline)], whose fluorescence emission intensity is quenched by oxygen. The sensor was constructed from 1 cm to 5 cm of plastic optical fiber (POF) with 980 µm core diameter. For the fluorescent measurement it is use under high-intensity blue LED excitation. The sensor fabricated in found to response to different concentration of oxygen in both gaseous and aqueous stater. The sensor is also tairly linear.